FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE - Triswanti, Triswanti; Sari, Novi Maya; Nainggolan, Elfrida; Rahmawati, Rahajeng Siti Nur; Utami, Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: According to data from the Sei Tualang Raso Health Center in Tanjung Balai City in 2022, 100% of Fe tablets were given to registered pregnant women but only about 65% consumed Fe tablets according to the specified number of 90 tablets. In 2022 there were 620 cases of anemic pregnant women at the Puskesmas Sei Tualang Raso Tanjung Balai City. The purpose of the study was to determine the factors that influence the compliance of pregnant women in consuming Fe. This research is a quantitative study with a cross sectional study design. The research was conducted in the working area of the Sei Tualang Raso Health Center in July 2023. The analysis performed was univariate and bivariate analysis. The results showed there was a relationship between the role of officers (p value: 0.001) and family support (p value: 0.001) on compliance with Fe tablet consumption. It is recommended that the puskesmas continue to maintain information provision either through individual counseling during home visits or group counseling during posyandu implementation and the information received brings positive assumptions for improving health promotion in the future and provides counseling to pregnant women about Fe tablets, the impact, along with the benefits of Fe tablets for pregnant women.Keywords: Family Support, Pregnant Women, Fe Table.